2017
DOI: 10.1089/chi.2017.0019
|View full text |Cite
|
Sign up to set email alerts
|

Maternal History of Child Abuse and Obesity Risk in Offspring: Mediation by Weight in Pregnancy

Abstract: In this national, prospective cohort study, prepregnancy BMI partially explained an association between maternal physical abuse in childhood and obesity in preschool-age children. These findings underscore the importance of life-course exposures in the etiology of child obesity and the potential multi-generational consequences of child abuse. Research is needed to determine whether screening for childhood abuse and treatment of its sequelae could strengthen efforts to prevent obesity in mothers and their child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…However, researchers have recently turned their attention toward the transmission of ACEs across generations, whereby parental ACEs confer risk for their children’s physical (Ximenes et al, 2019) and mental health (Kumar et al, 2018), social-emotional development (Folger et al, 2017; Madigan et al, 2017; (McDonnell & Valentino, 2016), and behavioral health problem (Esteves et al, 2020; Poehacker et al, 2020). For example, the children of individuals who were exposed to maltreatment during their own childhood have shown increased susceptibility to obesity (Leonard et al, 2017; Lindsay et al, 2020) and asthma (Condon et al, 2019; Lê-Scherban et al, 2018) in their offspring. Maternal ACEs were shown to be associated with internalizing and externalizing behavioral problems in children at 5 years of age (Cooke et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, researchers have recently turned their attention toward the transmission of ACEs across generations, whereby parental ACEs confer risk for their children’s physical (Ximenes et al, 2019) and mental health (Kumar et al, 2018), social-emotional development (Folger et al, 2017; Madigan et al, 2017; (McDonnell & Valentino, 2016), and behavioral health problem (Esteves et al, 2020; Poehacker et al, 2020). For example, the children of individuals who were exposed to maltreatment during their own childhood have shown increased susceptibility to obesity (Leonard et al, 2017; Lindsay et al, 2020) and asthma (Condon et al, 2019; Lê-Scherban et al, 2018) in their offspring. Maternal ACEs were shown to be associated with internalizing and externalizing behavioral problems in children at 5 years of age (Cooke et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, neither childhood social class, as indicated by deprivation level of the family, nor maternal mental disorders explained the associations we found between maternal BMI with offspring psychopathology. On the other hand, maternal exposure to childhood maltreatment may also have contributed: Exposure to childhood maltreatment is associated with obesity risk 11 , also in pregnant women 46 , and childhood maltreatment predicts increased psychopathology risk both within the same 47 and the next 48 , 49 generation. A Mendelian randomization study suggests the effects on mental health within the same generation may be causal 50 .…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] For example, studies have shown associations between parental experience of 1 or more ACEs and increased risk for overweight/obesity, cardiovascular disease, asthma, and poor overall health among their children. 4,5,[8][9][10][11] However, the pathway(s) by which intergenerational transmission occurs between parental ACEs and child weight is unknown. It is likely that parental ACEs are linked to child weight through several factors (eg, behavioral, psychological, biological) 5,6,8,12 that co-occur simultaneously, such as parent feeding practices, [13][14][15][16][17][18][19] parent physical activity (PA) practices, [19][20][21] parental weight, 7,8,22,23 and parental mental health.…”
Section: Introductionmentioning
confidence: 99%
“…(6) Did you often or very often feel that your parents were too drunk or high to take care of you?(7) Was your mother or stepmother often or very often pushed, grabbed, slapped, or had something thrown at her? (8) Did a parent or other adult in the household often or very often swear at you, insult you, put you down, or humiliate you?(9) Were you physically abused by a parent or guardian?(10) Were you sexually abused by a parent or guardian?(11) Were you sexually abused by someone who was not a parent or guardian? Response options were "Yes" or "No."…”
mentioning
confidence: 99%